2021
DOI: 10.1051/0004-6361/202140516
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and present surface evolution processes in the Ash region of comet 67P/Churyumov-Gerasimenko

Abstract: Aims. The Rosetta mission provided us with detailed data of the surface of the nucleus of comet 67P/Churyumov-Gerasimenko. In order to better understand the physical processes associated with the comet activity and the surface evolution of its nucleus, we performed a detailed comparative morphometrical analysis of two depressions located in the Ash region. Methods. To detect morphological temporal changes, we compared pre- and post-perihelion high-resolution (pixel scale of 0.07–1.75 m) OSIRIS images of the tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…The occurrence of outgassing events increases when the comet approaches the Sun because the solar insulation increases. At each perihelion passage, the comet loses material (Pätzold et al 2018), leading to the apparition of new morphological features or changes in existing ones (Groussin et al 2015b;El-Maarry et al 2017;Bouquety et al 2021).…”
Section: Cometary Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The occurrence of outgassing events increases when the comet approaches the Sun because the solar insulation increases. At each perihelion passage, the comet loses material (Pätzold et al 2018), leading to the apparition of new morphological features or changes in existing ones (Groussin et al 2015b;El-Maarry et al 2017;Bouquety et al 2021).…”
Section: Cometary Environmentmentioning
confidence: 99%
“…Several of these morphologies can be identified as depressions. In order to select the most appropriated ones, which will become our baseline for the comparison with 67P, we list here the terrestrial and Martian permafrost depressions identified in the literature, and compare their characteristics with the two depressions studied in Bouquety et al (2021). Four main types of permafrost depressions exist on Earth and Mars (French 2007;Hargitai & Kereszturi 2015).…”
Section: Permafrost Depressions On Earth and Marsmentioning
confidence: 99%
See 3 more Smart Citations